PERAN PENGAWAS SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SD NEGERI SEKTOR BARAT KECAMATAN JANGKANG KABUPATEN SANGGAU - Syabirin; Wicaksono , Luhur; Zakso , Amrazi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study describes the role of school supervisors in improving the quality of education in public elementary schools in the Western region of Jangkang District, Sanggau Regency, which faces challenges such as difficult geographical conditions and limited resources. Using a qualitative approach with a case study design, the study involves 10 participants from 3 elementary schools, consisting of 2 females and 8 males aged 32–57 years. Data collection methods include in-depth interviews, direct observations, and document analysis. The findings show that school supervisors play a crucial role in academic supervision, teacher professional development, and educational quality evaluation. These roles are carried out through direct visits, training sessions, and facilitating communication among educators. However, supervision effectiveness is hindered by geographical constraints, a limited number of supervisors, and inadequate facilities. To address these challenges, supervisors implement cluster-based strategies and utilize communication technology, such as WhatsApp. The study also found improvements in students’ literacy and numeracy skills, although overall competency levels remain in the lower-middle category. In conclusion, school supervisors play a vital role in enhancing educational quality despite significant challenges. Innovation and strategic policies are needed to strengthen supervision in remote areas to achieve more equitable education standards.